문서 기록으로 남겨진 참 예언자와 거짓 예언자: 예언자 평가에 대한 사회사적 문헌사적 접근 - 오민수(Min-Su Oh) (구약논단, 2023)
신명기 18장 15-22절은 왕국의 공무원인 선지자의 자격을 논하는 것이기보다는, 이스라엘의 요구에 응하시는 하나님과 하나님의 말씀의 성취를 기다리는 백성들의 자세에 마지막 초점을 두고 있다. 참 예언과 거짓 예언은 이방신의 이름으로 시행될 경우 명확히 판명되며, 야훼의 선지자일 경우 당대 사람들로서는 사건이 성취되기 전에까지 마지막까지 기다릴 것이 요청된다. 결국, 야훼는 반드시 – 어느 장소나 각 시대에 필요한(ubi et quando necesse est) – 모세와 같은 선지자를 일으킬 것이고, 야훼의 이름으로 전달된 예언은 야훼 자신과 같은 말의 권위로(신 18:19) 타당성이 있음을 말한다. 또한, 예언자의 품행에 있어서 모세(의 성품)와 같지 아니하며, 제멋대로 주제넘게 행동하는 자(신 18:20)는 최소한 야훼의 이름으로 행하지만, 거짓 예언일 수 있음을 예상케 한다. 야훼의 이름을 말하지만 자기 마음에 있는 것으로 꾸며내어 오만하게 예언하는 자들을 역사를 주관하시는 하나님은 시간(시절)을 두고 반드시 엄중히 다루신다. - 너는 네 하나님 야훼의 이름을 헛되게 입에 올리지 말지라. 야훼는 자신의 이름을 헛되이 입에 올리는 자를 처벌하지 않고 두지는 않으심이라! (신 5:11). 반면, 참 예언의 말씀은 역사 조성의 능력이 있을 뿐만 아니라, 점진적으로 성취되기에 마지막까지 기다려야 한다. 다만, 어떤 예언이든 공표된 예언은 작은 문서의 형식이나 구전의 형식으로 깨어있는 제자 그룹에 의해 보관되고, 이후에 예언된 사건이 역사적으로 성취될 경우, 이를 문서화해서 후대 사람들에게 증험이 있는 야훼 살아있는 말씀으로 읽히게 한다. 당대 수신자들에게 예언(자)의 진위(眞僞) 여부는 예언자 내부 분쟁이나 갈등으로 보여졌을 것이다. 복잡한 인생의 통합적인 측면을 마소라 본문은 간파하고 있으며 거짓 선지자 대신, 허위 정보나 (사실을 알고 있지만, 또 다른 개인적 목적을 가지고) 기만하는 메시지를 전달하는 사람들을 개념어, sheker란 용어를 사용한다. 거짓 예언자는 없고, 다만 거짓된 예언을 하는 ‘그릇된 사람만’이 존재한다. pseudoprophetes란 용어가 처음 도입된 것은 BC 1세기경 LXX의 번역이었다. Deuteronomy 18:15-22 does not discuss the qualifications of a prophet as an official of the kingdom, but rather focuses on God responding to Israel’s demands and the attitude of the people waiting for the fulfillment of God’s word. True prophecies and false prophecies are clearly identified when they are implemented in the name of a foreign god, and in the case of Yahweh's prophets, the people of the time are asked to wait until the end until the event is fulfilled. After all, Yahweh will surely - in every place and at every age (ubi et quando necesse est) - raise up prophets like Moses, and prophecies delivered in Yahweh's name, with the authority of words like Yahweh himself (Deut 18:19) indicates that there is validity. Also, it is expected that the prophet’s behavior is not like Moses’ (character), and he who behaves presumptuously (Deut 18:20) at least acts in the name of Yahweh, but may be a false prophecy. God, who speaks the name of Yahweh, but fakes what is in his heart and prophesies arrogantly, God, who governs history, must deal it with times and severely - You shall not speak the name of Yahweh your God in vain. Yahweh does not leave unpunished those who speak his name in vain! (Deut. 5:11). On the other hand, the words of true prophecy not only have the ability to create history, but also have to wait until the end because they are gradually fulfilled. However, any prophecy that has been announced is kept by a group of awakened disciples in the form of a small document or oral tradition, and later, if the prophesied event is historically fulfilled, it is documented and Yahweh living as a testament to future generations. to be read in words. To the recipients of the time, the authenticity of the prophecy would have been seen as an internal dispute or conflict within the prophecy. The Masoretic text penetrates the integrative aspect (synthetische Lebensauffassung) of complex life, and instead of false prophets, people who deliver false information or deceptive messages (knowing the facts, but with another personal purpose) are the concept word, ‘sheker’. The term is used. There are no false prophets, only ‘false men’ who prophesy falsely. The term false prophet (pseudoprophetes) was first introduced in a translation of the LXX around the 1st century BC. KCI Citation Count: 0